Lipid peroxidation marker in saliva of Type 2 Diabetes Mellitus with oral manifestations – A Clinical and biochemical study. - Madi, Medhini; Babu, Subhas G; Kumari, Suchetha; Shetty, Shishir Ram; Bhat, Supriya; Castelino, Renita (Bangladesh Journal of Medical Science, 2018)
Background: Type 2 Diabetes progresses gradually and in a stepwise order. It commences with insulin resistance and progresses slowly with time until the body fails to maintain glucose homeostasis. These alterations are accompanied with changes in lipid peroxidation. The determination of the oxidative stress requires sometimes invasive techniques. Exploring saliva for oxidative stress has great clinical interest Objective: The present study was undertaken to estimate, compare and correlate the levels of malondialdehyde (MDA) in the serum and saliva of patients with type 2 diabetes mellitus with oral manifestations and healthy controls. Materials and Methods: Serum and salivary Malondialdehyde levels were estimated in 45 healthy subjects (Group I) and 45 patients with Type 2 Diabetes with oral manifestations (Group II). Estimation of Random blood sugar levels were done by GOD-PAP methodology. The data obtained from the present study was analyzed using SPSS software. Independent T test was used to compare the levels in the study and control group. Pearson’s correlation coefficient was used to correlate the changes in serum and saliva. P< 0.05 was considered significant. Results:The mean serum Malondialdehyde levels in Group I was 0.958 μM/l, while the mean serum Malondialdehyde levels of Group II was 2.828 μM/l. The mean salivary Malondialdehyde levels in Group I was 0.217 μM/l, while the mean salivary Malondialdehyde levels of Group II was 0.688μM/l. The mean serum and salivary Malondialdehyde levels were significantly increased in subjects with Type 2 Diabetes with oral manifestations in comparison to the healthy subjects. Fair positive correlation was observed between serum and salivary Malondialdehyde levels in Group I (r = 0.341) and very good positive correlation was observed between serum and salivary Malondialdehyde levels in Group II (r = 0.613). Conclusion: Serum and salivary Malondialdehyde was significantly higher in subjects with Type 2 Diabetes Mellitus with oral manifestations when compared to healthy controls. The increase in serum and salivary levels of MDA, shows that free radicals are formed disproportionately in diabetes mellitus by glucose degradation, non-enzymatic glycation of proteins, and the subsequent oxidative degradation, which may play an important role in the development of complications in diabetic patients. Fair positive correlation was found between serum and salivary Malondialdehyde in healthy subjects and very good positive correlation was observed between serum and salivary Malondialdehyde in subjects with Type 2 Diabetes Mellitus with oral manifestations. This study highlights that type 2 diabetic patients undergo abnormally high levels of oxidative stress. Hence exploring saliva for oxidative stress is of great importance. Thus saliva could be used as a reliable, non-invasive tool in the assessment of oxidative status. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.644-651